Gadamer's repercussions : reconsidering philosophical hermeneutics - Krajewski, Bruce, 1959- (Berkeley, Calif. : University of California Press, 2004)
German philosopher Hans-Georg Gadamer influenced the study of literature, art, music, sacred and legal texts and medicine. This volume brings together many prominent scholars to assess, re-evaluate and question Gadamer's works, as well as his place in intellectual history.
From word to concept: the task of hermeneutics as philosophy / Hans-Georg Gadamer -- After historicism, is metaphysics still possible? on Hans-Gerog Gadamer's 100th birthday / Jürgen Habermas -- Being that can be understood is language / Richard Rorty -- On the coherence of hermeneutics and ethics: an essay on Gadamer and Levinas / Gerald L. Bruns -- Gadamer and romanticism / Andrew Bowie -- Literature, law, and morality / Georgia Warnke -- A critique of Gadamer's aesthetics / Michael Kelly -- On dialogue: to its cultured despisers / Donald G. Marshall -- Gadamer's philosophy of dialogue and its relation to the postmodernism of Nietzsche, Heidegger, Derrida, and Strauss / Ronald Beiner -- Meaningless hermeneutics? / Joel Weinsheimer -- Radio Nietzsche, or, how to fall short of philosophy / Geoff Waite -- The art of allusion: Hans-Georg Gadamer's philosophical interventions under National Socialism / Teresa Orozco -- On the politics of Gadamerian hermeneutics: a response to Orozco and Waite / Catherine H. Zuckert -- The protection of the philosophical form: a response to Zuckert / Teresa Orozco -- Salutations: a response to Zuckert / Geoff Waite.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Gadamer, Hans-Georg, -- 1900-2002.; Gadamer, Hans-Georg, -- 1900-2002; PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- Political